PEMBELAJARAN KIMIA MENGGUNAKAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT DITINJAU DARI KREATIVITAS DAN KEMAMPUAN BERPIKIR KRITIS - Restiana Purwaningtyas; - Ashadi; - Suparmi (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2014)
The purposes of the research were to know the difference  between student cognitive achievement  who learnt chemistry learning achievement using Science Technology Society between student who had high and low creativity, between student who had high and low critical thinking and their interaction. The research used experimental method. The data was collected using test for cognitiveachievement, creativity and critical thingking and questionnaire for student affective achievement. The data was analyzed using non-parametric Kruskal Wallis. Based on the results of data analysis it can be concluded that: 1) there was difference in students’ cognitive achievement between student who had high and low creativity, 2) there was no difference in students’ cognitive achievement between student who had high and low critical thinking, 3) there was an interaction between STS with creativity toward student’s cognitive achievement, 4) there was no an interaction between STS with critical thinking toward students' cognitive achievement, 5) there was no interaction between creativity and critical thingking toward student’s cognitive achievement.Keywords: Science Technology Society, Creativity, Critical Thinking, Acid Base, Student CognitifAchievement.